KNOWLEDGE MANAGEMENT PADA WEBSITE ILMUKOMPUTER. COM - Amelia, Vita (Universitas Lancang Kuning, 2013)
Knowledge Management is series of processes which is developed in an organization to create, to collect, to maintain and to disseminate the knowledge of the knowledge itself. The scopes of Knowledge management are: Creation, Utilizat ion Storing, Distribution/Sharing, Structure, Technology, Measurement, Organizational Design , Leadership, and Culture. Ilmukomputer.Com is an eLearning community that share literahrres and materials freely in computer field. The main mission of this community is to take prut to teach people, especially in computer education. Knowledge management in an organization such as in library, university, company dan even website is needed. Knowledge sharing is also nee ded in website either for individual need or for website branding.